2015
DOI: 10.5897/ajb2015.14400
|View full text |Cite
|
Sign up to set email alerts
|

Oil palm fruit fibre promotes the yield and quality of Lentinus squarrosulus (Mont.) Singer, an edible Nigerian mushroom

Abstract: Agricultural production and the agro-food industry furnish large volumes of solid wastes, which when unutilized could lead to environmental pollution. An attempt was made to utilize wastes from the oil palm and timber industries for the cultivation of Lentinus squarrosulus, a Nigerian edible mushroom. Mahogany sawdust (MSD), Gmelina sawdust (GSD), oil palm fruit fibre (OPFF) and oil palm empty fruit bunch (OPEFB) significantly influenced crop cycle time, yield, nutritional properties and market quality of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
1
2
Order By: Relevance
“…Effect of different wood wastes on the growth parameters of L. squarrossulus: The fresh mean weight (9.13 kg -19.00 kg) of L. squarrosulus obtained from this study in table 3 is greater than the result (1.98 -7.26), provided by Osibe and Chiejina, (2015). The pileus diameter value (3.03 cm -4.64 cm) obtained was similar to the report (3.01 -5.76), given by Chiejina and Osibe, (2015), but higher than the findings of Nwanze, et al, (2005), who reported a range of 1.07 cm -4.37cm…”
Section: Effects Of Mineral Composition Of Sawdust On the Proximate A...contrasting
confidence: 55%
See 2 more Smart Citations
“…Effect of different wood wastes on the growth parameters of L. squarrossulus: The fresh mean weight (9.13 kg -19.00 kg) of L. squarrosulus obtained from this study in table 3 is greater than the result (1.98 -7.26), provided by Osibe and Chiejina, (2015). The pileus diameter value (3.03 cm -4.64 cm) obtained was similar to the report (3.01 -5.76), given by Chiejina and Osibe, (2015), but higher than the findings of Nwanze, et al, (2005), who reported a range of 1.07 cm -4.37cm…”
Section: Effects Of Mineral Composition Of Sawdust On the Proximate A...contrasting
confidence: 55%
“…The L. squarrossulus with the least moisture content indicated that it can be easily sundried, smoked and stored soon after harvest. The value obtained in this experiment is very low when compared to the values (12.28 -13.33) documented by Chiejina and Osibe, (2015), but can be likened to (9.88 -10.67) described by Nwoko, et al, (2018). More so, it was greater than the value (6.87 -8.75%) obtained when P. ostreatus was cultivated on the same substrates .…”
Section: Effects Of Mineral Composition Of Sawdust On the Proximate A...supporting
confidence: 54%
See 1 more Smart Citation
“…It has been estimated that the number of mushrooms on earth is about 140,000 yet only 14,000 (10%) are known (Hawksworth, 2001). One of the values of commercial cultivation of mushrooms, especially in a developing economy like Nigeria, is the availability of large quantities of several agroindustrial wastes which can serve as substrate for the cultivation of mushrooms (Banjo et al, 2004;Chiejina, 2015). A substrate is any substance that can facilitate mycelia growth.…”
Section: Introductionmentioning
confidence: 99%